From being diverse to becoming diverse: A dynamic team diversity theory. (23rd February 2018) - Li, Jia; Meyer, Bertolt; Shemla, Meir; Wegge, Jürgen
Summary: On the basis of the literature of open systems and team diversity, we present a new dynamic team diversity theory that explains the effect of change in team diversity on team functioning and performance in the context of dynamic team composition. Building upon the conceptualization of teams as open systems, we describe the enlargement and decline of team variety, separation, and disparity through member addition, subtraction, and substitution. Then, focusing on diversity enlargement, we theorize the contemporaneous and lasting effects of team diversity change on team performance change and on team processes and states leading to them. Dynamic team diversity theory expands the focus of team diversity research from teams' being more diverse than others to teams' becoming more diverse than before. It aims to advance team diversity research to be better aligned with the organizational reality of dynamic team composition. We also discuss methodological considerations in subsequent empirical testing of the theory and highlight how the theory and future research may help to guide organizational practice in recomposing work teams.